Examining the Relationship Between Adaptability, Social Support, and Psychological Wellbeing Among Chinese International Students at UK Universities - Holliman, Andrew; Waldeck, Daniel; Yang, Tiange; Kwan, Cheuk; Zeng, Manting; Abbott, Nicola (Frontiers in Education, 2022)
University entry represents a period of significant change for students. The extent to which students are able to effectively navigate this change (e.g., via their personal adaptability and social support) will likely impact upon their psychological wellbeing (a finding corroborated by recent studies). However, no study to date has examined these relations among overseas, international students, who represent an increasing proportion of university students in the UK and where the degree of change, novelty, and uncertainty is often exacerbated. In the present study, 325 Chinese international (overseas) students at UK universities, were surveyed for their adaptability and social support as well as their psychological wellbeing outcomes (e.g., life satisfaction, flourishing, and distress). A series of moderated regression analyses revealed that adaptability and social support operate largely as independent predictors of psychological wellbeing (all outcomes). Further, social support was found to moderate the association between adaptability and two of the psychological wellbeing outcomes: life satisfaction and psychological distress. These findings have important implications for educators and researchers, who are seeking to support the transition of international (overseas) students to university and optimize their experience.